2021
DOI: 10.52403/ijrr.20210627
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status of Special Children in Tribal Population of Southern India

Abstract: Introduction: The oral health needs of intellectually disabled are complex and may be related to underlying congenital or developmental anomalies as well as the inability to receive adequate personal and professional care to maintain. This research suggests that people with Intellectually Disability such as Mental retardation, are more likely to have poor oral hygiene, periodontal diseases and high incidence of trauma and possibly more likely to have caries than people without Intellectual disability. Aim: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…(Dahal, Shrestha, and Bhagat 2018) In children with intellectual disabilities, the study results showed that other factors influencing the respondents' skills in cleaning dental plaque were the primary characteristics factors of children, excellent motor skills. (Sandy, Priyono, and Widyanti 2016) In an oral health status study conducted by Naveen et al with the target of children with intellectual disabilities, it was stated that 87.1% of children with disabilities (study group) had periodontal problems/conditions due to poor maintenance of oral hygiene.. (Katragadda, V, and Durga Mahendra 2021).…”
Section: Personal Cleanliness Problems In Children With Disabilitiesmentioning
confidence: 99%
“…(Dahal, Shrestha, and Bhagat 2018) In children with intellectual disabilities, the study results showed that other factors influencing the respondents' skills in cleaning dental plaque were the primary characteristics factors of children, excellent motor skills. (Sandy, Priyono, and Widyanti 2016) In an oral health status study conducted by Naveen et al with the target of children with intellectual disabilities, it was stated that 87.1% of children with disabilities (study group) had periodontal problems/conditions due to poor maintenance of oral hygiene.. (Katragadda, V, and Durga Mahendra 2021).…”
Section: Personal Cleanliness Problems In Children With Disabilitiesmentioning
confidence: 99%